2005
DOI: 10.1097/01.hp.0000144567.83125.00
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Gamma Spectrometry Measurements and Monte Carlo Computations for the Detection of Radioactive Sources in Scrap Metal

Abstract: A very limited number of field experiments have been performed to assess the relative radiation detection sensitivities of commercially available equipment used to detect radioactive sources in recycled metal scrap. Such experiments require the cooperation and commitment of considerable resources on the part of vendors of the radiation detection systems and the cooperation of a steel mill or scrap processing facility. The results will unavoidably be specific to the equipment tested at the time, the characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 3 publications
0
24
0
Order By: Relevance
“…A number of detector materials, such as 6 LiI or 3 He, have large low-energy neutron cross-sections that vary inversely with the neutron velocity. The high sensitivity of detectors based on these materials to slow neutrons can be advantageous since the lower energy neutrons may more likely be encountered in the search for illicit sources due to moderation from cargo.…”
Section: Neutron Detectorsmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of detector materials, such as 6 LiI or 3 He, have large low-energy neutron cross-sections that vary inversely with the neutron velocity. The high sensitivity of detectors based on these materials to slow neutrons can be advantageous since the lower energy neutrons may more likely be encountered in the search for illicit sources due to moderation from cargo.…”
Section: Neutron Detectorsmentioning
confidence: 99%
“…Radiation portal monitor (RPM) systems have been deployed to detect illicit trafficking in radioactive materials at international border crossings over the last several years [1]. Such systems have also long been used for safeguards applications [2] and for screening of scrap metal [3]. These large, passive detection systems are currently based upon panels of polyvinyl toluene plastic scintillator for gammaray detection and pressurized 3 He-based neutron detector tubes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such detectors have also long been used for safeguards applications and for screening of scrap metal [3]. It has been observed that large polyvinyl toluene (PVT)-based gamma ray detectors can suffer internal "fogging" when subject to years of outdoor exposure, resulting in changes to performance.…”
Section: Introductionmentioning
confidence: 99%
“…The determination of the minimum detection limits (MDL) of homogeneously contaminated scrap metal or of shielded sources embedded in scrap metal loads is currently an important topic of research and investigation [1]. Furthermore, the estimation of the radiological risk for both workers and public in the case that a non-detectable radioactive source enters the manufacturing process is of great interest.…”
Section: Introductionmentioning
confidence: 99%